SUNFLOWER OIL BLEACHING BY ACID-ACTIVATED BENTONITE - Luiz Foletto, Edson (2007)
Two bentonite clays with difierent mineralogical compositions from Mendoza, Argentine, were activated with H2SO4 solutions of 4 and 8 N at 90ºC for 3.5 hours. This treatment affected clay structural properties as was shown by thermogravimetry, infrared spectrometry and chemical analysis. Bleaching efficiency for sunflower oil was strongly dependent on acid concentration used for clay activation. The samples have bleaching capacity comparable to the standard. The mineralogical composition of natural clays has influenced the properties of activated clays.